Cell Penetrating Peptide: Sequence-Based Computational Prediction for Intercellular Delivery of Arginine Deiminase - Zarei, Mahboubeh; Rahbar, Mohammad R.; Negahdaripour, Manica; Morowvat, Mohammad Hossein; Nezafat, Navid; Ghasemi, Younes (Current Proteomics, 2020)
Background: Cell-Penetrating Peptides (CPPs), a family of short peptides, are broadly used as the carrier in the delivery of drugs and different therapeutic agents. Thanks to the existence of valuable databases, computational screening of the experimentally validated CPPs can help the researchers to select more effective CPPs for the intercellular delivery of therapeutic proteins. Arginine deiminase of Mycoplasma hominis, an arginine-degrading enzyme, is currently in the clinical trial for treating several arginine auxotrophic cancers. However, some tumor cells have developed resistance to ADI treatment. The ADI resistance arises from the over-expression of argininosuccinate synthetase 1 enzyme, which is involved in arginine synthesis. Intracellular delivery of ADI into tumor cells is suggested as an efficient approach to overcome the aforesaid drawback. Objective: In this study, in-silico tools were used for evaluating the experimentally validated CPPs to select the best CPP candidates for the intracellular delivery of ADI. Results: In this regard, 150 CPPs of protein cargo available at CPPsite were retrieved and evaluated by the CellPPD server. The best CPP candidates for the intracellular delivery of ADI were selected based on stability and antigenicity of the ADI-CPP fusion form. The conjugated forms of ADI with each of the three CPPs including EGFP-hcT (9-32), EGFP-ppTG20, and F(SG)4TP10 were stable and nonantigenic; thus, these sequences were introduced as the best CPP candidates for the intracellular delivery of ADI. In addition, the proposed CPPs had appropriate positive charge and lengths for an efficient cellular uptake. Conclusion: These three introduced CPPs not only are appropriate for the intracellular delivery of ADI, but also can overcome the limitation of its therapeutic application, including short half-life and antigenicity.
Keywords: therapeutic protein